Safety and efficacy of mirabegron in daily clinical practice: a prospective observational study. (August 2016) - Kallner, Helena Kopp; Christensson, Anna Almén; Elmér, Caroline; Flam, Benjamin; Altman, Daniel
Abstract: Objective: To determine risks associated with prescribing mirabegron, the first-in-class β3 -adrenoreceptor agonist, to non-selected female patients with overactive bladder. Study design: Routine female patients seeking treatment for overactive bladder ( n = 221) in a urology/gynecology outpatient clinic. Data on adverse events, cardiovascular outcomes, condition specific symptoms and drug discontinuation was collected at two months follow-up (FU). Non-parametric statistics was used as appropriate. Odds ratios (ORs) with 95% confidence intervals (CIs) for outcome association analyses using logistic regression. Results: 16 patients (7.2%) discontinued treatment because of side effects. There were no significant associations between cardiovascular adverse events and pre-existing cardiovascular disease (OR 0.3, 95% CI 0.3–2.6), or pre-existing ECG abnormalities (OR 2.3, 95% CI 0.3–16.3). At FU ECGs there were no de novo cases of tachyarrhythmias and no significant difference in mean QTc between baseline (403 ms, SD 21.7) and the 2 months follow-up ECG (403 ms, SD 20.3) ( p = 0.75). There was a significant decrease in the mean systolic blood pressure ( p = 0.03) but no significant change in mean diastolic pressure ( p = 0.8) or heart rates ( p = 0.2) from baseline to FU. Overactive bladder specific symptoms and quality of life improved significantly ( p < 0.001 respectively). Conclusions: Mirabegron treatment is associated with a satisfactory cardiovascular safety profile, as well as, significant symptomatic improvement also in a heterogeneous population of non-selected women with overactive bladder presenting in everyday clinical practice.